Penguatan Kompetensi Pedagogik dan Digital Guru Pesantren melalui Pelatihan Artificial Intelligence berbasis Model ASSURE di Kabupaten Pasuruan - Nur Fitria Anggrisia; Habiba Al Umami; Septia Dwi Jayanti (Nawadeepa: Jurnal Pengabdian Masyarakat, 2026)
The development of artificial intelligence (AI) in education has opened up new opportunities for teachers to create learning that is more interactive, effective, and adaptive to student needs. However, the use of AI in Islamic boarding school-based education environments is still relatively limited due to low digital literacy, minimal training, and teachers' lack of experience in integrating technology into learning. This service activity aims to improve the pedagogical and digital competence of Islamic boarding school teachers through training in the use of artificial intelligence applications based on the ASSURE model. The activity was carried out at the ABM Islamic Boarding School (pseudonym), Pasuruan Regency, involving 53 teachers from various subjects. Implementation of activities includes observing participant needs, workshops, demonstrations of using AI applications, independent practice, mentoring, microteaching, and evaluation. Activity data was obtained through observation, pre- and post-training questionnaires, documentation, and participant reflection. The results of the activity show an increase in teacher competence in using AI for learning. Before the training, only 12 teachers (22.6%) had ever used AI applications in learning, and 18 teachers (34.0%) felt confident using digital technology. After training, 47 teachers (88.7%) understood the basic concepts of AI in learning, 44 teachers (83.0%) were able to use AI applications, and 45 teachers (84.9%) felt more confident using digital technology. In addition, 50 teachers (94.3%) stated that training helped improve the quality of learning. Applications used include ChatGPT, Grammarly, Google Classroom, Canva AI, and Quizizz AI to organize material, make evaluations, develop visual media, and design interactive learning activities. This activity contributes to showing that direct practice-based AI training using the ASSURE model can be an effective strategy for strengthening the pedagogical and digital competencies of Islamic boarding school teachers. This program recommends ongoing training and mentoring to support the digital transformation of learning in the Islamic boarding school environment.